Privatization and Profit Efficiency: Evidence from Commercial Banks of Pakistan - Sabir, Samina; Qayyum, Abdul (Journal of Asian Business Strategy, 2018)
This paper investigates the profit efficiency of commercial banks where the banking sector has completed more than two decade of changeover from nationalization policy to privatization and restructuring policy by employing stochastic frontier true effect and true random effect models. Intermediation approach has been used to choose input and output variables of banks. A balanced panel data of 22 commercial banks of Pakistan over the period 1995-2014 have been used for the empirical analysis. The paper found that commercial banks are on average 73% profit efficient. However foreign banks report high profit efficiency score followed private domestic banks and then state owned banks. We also compared the cost and profit efficiency of commercial banks and found that commercial banks are more cost efficient than profit efficient.